Legal Protection for Parties in Making Authentic Deeds from Legal Deviations by Notaries - Himawan Arifin (Sultan Agung Notary Law Review, 2021)
The position of a Notary is required by laws and regulations with a view to assisting and serving the public who need authentic written evidence, but a Notary in carrying out his profession commits a crime of forgery of letters in making an authentic deed so that a Notary who is consciously, intentionally or involved in making fake authentic deeds can be accounted for in criminal law. This writing aims to find out the legal protection for the victim who is harmed in making an authentic deed containing false information and the notary's responsibility in making the deed. The research method used in this thesis is a normative juridical approach, namely legal research carried out based on the main legal material by examining theories, concepts, legal principles and legislation related to research, this approach is also known as with a library approach, namely studying books, laws and regulations and other documents related to this research. The results of the study found that the Notary in making an authentic deed had fulfilled the elements of the criminal act of forging letters against an authentic deed in Article 263 paragraph 1 and Article 264 paragraph 1 to 1 of the Criminal Code. Legal protection for the victim takes legal action by reporting to the police and bringing the case to the Court of first instance, the level of appeal, and the level of cassation. So that the Notary is charged with responsibility in the form of imprisonment because it has been legally proven guilty of committing a criminal act of forging letters against an authentic deed.